Comparison of Rigid Pavement Planning Using PD T-14-2003 and NAASRA 1987 Methods in Industrial Areas - Krisdiyanto, Aris; Dewi, Kemmala; Azis, Faruk (Malikussaleh University, Aceh, Indonesia, 2025)
As vital infrastructure, roads are a means of transportation access and function as a distribution route for goods and services. Road pavement plays a crucial role in highway construction, necessitating proper planning according to Indonesian standards and planning criteria to ensure smooth land transportation and provide comfort and safety for its users. This study aims to provide information on road conditions, drainage dimensions, and construction costs. Planning is crucial in every road construction design, particularly for rigid pavement, based on survey data collected from the road section. Numerous methods exist for calculating the design value of rigid pavement. We use the Pd T-14-2003 method and the NAASRA 1987 method (National Association of Australian State Road Authorities) to plan rigid pavement thickness in the industrial area of PT. Bukit Muria Jaya Kudus. The Pd T-14-2003 method yielded a JSKN of 4x107 and a CBR of 35% for the subgrade, resulting in a plate thickness of 150 mm. While the Naasra 1987 planning method achieved a JSKN of 6x107 and a CBR of 35% for the base soil, a plate thickness of 160 mm was obtained with a value of K = 80 kPa/mm. The reinforcement planning using the Pd T-14-2003 and Naasra 1987 methods involves longitudinal reinforcement D10 mm at a distance of 150 mm and transverse reinforcement D10 mm at 250 mm. The drainage dimensions at the cross-section location are width x height (1 m x 1 m), and the guard's height is 0.2 m.